Summer rainfall DOC, solute and sediment fluxes in a small Arctic coastal catchment on Herschel Island (Yukon Territory, Canada) - Coch, Caroline; Lamoureux, Scott F.; Knoblauch, Christian; Eischeid, Isabell; Fritz, Michael; Obu, Jaroslav; Lantuit, Hugues (NRC Research Press (a division of Canadian Science Publishing), 2018)
Coastal ecosystems in the Arctic are affected by climate change. As summer rainfall frequency and intensity are projected to increase in the future, more organic matter, nutrients and sediment could be mobilized and transported into the coastal nearshore zones. However, knowledge of current processes and future changes is limited. We investigated streamflow dynamics and the impacts of summer rainfall on lateral fluxes in a small coastal catchment on Herschel Island in the western Canadian Arctic. For the summer monitoring periods of 2014-16, mean dissolved organic matter (DOM) flux over 17 days amounted to 82.7 Âą 30.7 kg km-2 and mean total dissolved solids flux to 5252 Âą 1224 kg km-2. Flux of suspended sediment (SS) were 7245 kg km-2 in 2015, and 369 kg km-2 in 2016. We found that 2.0 % of SS was composed of particulate organic carbon. Data and hysteresis analysis suggests a limited supply of sediments; their interannual variability is most likely caused by short-lived localized disturbances. In contrast, our results imply that DOC is widely available throughout the catchment and exhibits positive linear relationship with runoff. We hypothesize that increased projected rainfall in the future will result in a similar increase of DOC fluxes. The accepted manuscript in pdf format is listed with the files at the bottom of this page. The presentation of the authors' names and (or) special characters in the title of the manuscript may differ slightly between what is listed on this page and what is listed in the pdf file of the accepted manuscript; that in the pdf file of the accepted manuscript is what was submitted by the author.